High Glucose-Induced Cardiomyocyte Damage Involves Interplay between Endothelin ET-1/ETA/ETB Receptor and mTOR Pathway - Pandey S. (2023)
Patients with type two diabetes mellitus (T2DM) are at increased risk for cardiovascular diseases. Impairments of endothelin-1 (ET-1) signaling and mTOR pathway have been implicated in diabetic cardiomyopathies. However, the molecular interplay between the ET-1 and mTOR pathway under high glucose (HG) conditions in H9c2 cardiomyoblasts has not been investigated. We employed MTT assay, qPCR, western blotting, fluorescence assays, and confocal microscopy to assess the oxidative stress and mitochondrial damage under hyperglycemic conditions in H9c2 cells. Our results showed that HG-induced cellular stress leads to a significant decline in cell survival and an impairment in the activation of ETA-R/ETB-R and the mTOR main components, Raptor and Rictor. These changes induced by HG were accompanied by a reactive oxygen species (ROS) level increase and mitochondrial membrane potential (MMP) loss. In addition, the fragmentation of mitochondria and a decrease in mitochondrial size were observed. However, the inhibition of either ETA-R alone by ambrisentan or ETA-R/ETB-R by bosentan or the partial blockage of the mTOR function by silencing Raptor or Rictor counteracted those adverse effects on the cellular function. Altogether, our findings prove that ET-1 signaling under HG conditions leads to a significant mitochondrial dysfunction involving contributions from the mTOR pathway.